03.16 Regulatory t cells restrain autophagy in dendritic cells to ameliorate autoimmunity in a ctla4 dependent fashion. (1st March 2017) - Alissafi, Themis; Banos, Aggelos; Boon, Louis; Sparwasser, Tim; Vassilopoulos, Dimitrios; Boumpas, Dimitrios; Chavakis, Triantafyllos; Cadwell, Kenneth; Verginis, Panayotis
Abstract : Background: Design of efficacious regulatory T cell (Tregs)-based therapies and establishment of clinical tolerance in autoimmune diseases has proven to be challenging. The clinical implementation of Treg immunotherapy has been hampered by various impediments concerning the stability and isolation procedures of Tregs but also the specific in vivo targets of Treg modalities. Materials and methods: Peripheral blood samples were obtained from patients diagnosed with RA according to the ACR criteria. RA patients were treated with anti-TNFα treatment or CTLA4-Ig (Abatacept-Orencia, Bristol-Myers Squibb). Experimental Autoimmune Encephalomyelitis was induced in mice with administration of myelin peptide Mog35-55 emulsified in CFA. Results: Herein, we demonstrate that Foxp3 + Tregs potently suppress autoimmune responses in vivo through inhibition of the autophagic machinery in DCs in a CTLA4-dependent manner. Autophagy deficient DCs exhibited reduced immunogenic potential and failed to prime autoantigen-specific CD4 + T cells to mediate autoimmunity. Mechanistically, CTLA4 binding promoted the activation of PI3K/Akt/mTOR axis and FoxO1 nuclear exclusion in DCs leading to decreased transcription of the autophagy component Lc3b . Notably CTLA4-Ig (Abatacept)-treated human DCs demonstrated reduced levels of autophagosome formation, while DCs from Abatacept treated rheumatoid arthritis (RA) patients displayed diminished Lc3b transcripts. Conclusions: Collectively, our data identify the canonical autophagy pathway in DCs as a novel molecular target of Foxp3 + Treg-mediated suppression leading to amelioration of autoimmune responses. These findings may pave the way for the development of therapeutic protocols exploiting Tregs for the treatment of autoimmunity as well as diseases that disturbed tolerance is a common denominator.